Emigration of rio grandens to Paraguay and the search for land property in networks (1970 -1980) (TEL Tempo, Espaço e Linguagem, 2023)
The present work intends to analyze the emigration of families from Rio Grande do Sul to districts of the Department of Alto Paraná, Paraguay, in the period from 1970 to 1980, aiming to understand the influence of social networks in the search for land ownership, of quality, in greater quantity and at an affordable price. This is an oral history work, which starts from the analysis of semi-structured interviews, carried out with immigrants in the border region of both countries. It is concluded that the presence of social networks, made up of neighbors, acquaintances and family members, who had already emigrated to Paraguay and who, upon returning, advertised about the lands of that country, was one of the important factors for the purchase of land and emigration. Key-words: Emigration. Rio-grandense. Paraguay.